"It's important, but…": Perceived Barriers and Situational Dependencies to Social Contact Preferences of Nursing Home Residents. (22nd June 2017) - Abbott, Katherine M; Bangerter, Lauren R; Humes, Sarah; Klumpp, Rachel; Van Haitsma, Kimberly
Abstract: Background and Objectives: U.S. Nursing homes (NH) are shifting toward a person-centered philosophy of care, where staff understand each residents preferences, goals and values, and seek to honor them throughout the care delivery process. Social interactions are a major component of life and while low rates of social interactions are typically found among NH residents, little research has examined resident preferences for specific types of social interactions. The purpose of this study is to explore, from the perspective of the NH resident, barriers to social contact preferences and situations when social preferences change. Research Design and Methods: Two interviews were conducted with 255 NH residents 3 months apart, recruited from 32 NHs using 13 social-contact items from the Preferences for Everyday Living Inventory-NH . Results: Content analysis of 1, 461 spontaneous comments identified perceived barriers to preference fulfillment along with reasons why residents would change their mind about the importance of a preference (situational dependencies). Nearly 50% of social preferences for choosing a roommate, having regular contact with friends, giving gifts, and volunteering were associated with barriers. Social preferences were likely to change based upon the quality of the social interaction and the resident's level of interest. Discussion and Implications: Knowledge of barriers regarding social preferences can inform care efforts vital to advancing the delivery of person-centered care. In addition, understanding the reasons why NH resident preferences change based upon context can help providers with staff training leading to individualized care and develop meaningful social programs that are in line with resident preferences.